Synthesis, Characterization And Antimicrobial Screening Of Novel Fused Heterocyclic Compounds - V. Talaviya, Purav; Chaudhari, J.A. (International Journal of Psychosocial Rehabilitation, 2020)
The 2-(2-bromo-1-(naphthalen-2-yl)ethylidene)malononitrile (2) synthesised by the reaction between 1-(naphthalen-2 yl)ethanone (1) with malononitrile. The compound (2) on reaction with substituted amines (3a-f) gives 2-amino-4 (naphthalen-2-yl)-1-aryl-1H-pyrrole-3-carbonitrile (4a-f). A series of 2-methyl-5-(naphthalen-2-yl)-7-aryl-3H-pyrrolo [2,3-d] pyrimidin-4(7H)-one derivatives (5a-f), when 2-amino-4-(naphthalen-2-yl)-1-aryl-1H-pyrrole-3-carbonitrile (4a-f) react with Ac2O in presence of pyridine. Synthesized compounds were characterized by IR, mass (MS) and 1H NMR spectra as well as elemental analysis. They were also screened for their in vitro antibacterial activity against Gram positive bacteria (Bacillus Subtilis Staphylococcus aureus, Gram-negative bacteria (Kllebsiella promioe, E.coil).